Sistem Pendukung Keputusan Pemilihan Staf Karyawan Bpn Terbaik Di Wilayah Kota Medan Dengan Mengunakan Metode Moora Dengan Pembobotan Roc - Munte, Joni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Decision Support System (DSS) is a decision support system that can help in handling or solving problems in a company or in the daily environment, in determining a problem we need data that we will take in a company or in the environment. In writing this is an example of a problem that is currently happening with the case study of the Selection of the Best BPN Employees in the City of Medan, therefore the author uses a method that will be able to find the best employee data, therefore the author creates a decision support system that will be able to determine the best BPN employee assessment process in the city of Medan. Where this system is a system that has a very important role in decision making. The system is DSS, where DSS is one of the systems that can assist in solving each problem by requiring data and methods contained in the DSS in order to obtain more relevant information and support in making each decision. In completing this research, the writer has to find the weight value of the criterion data where the writer uses the ROC method to produce the weight value and after that the writer also searches for the ranking value using the MOORA method. And where to produce ranking values in the MOORA method, the author must work according to predetermined steps in order to obtain precise and accurate reference values. The ROC and MOORA methods really help writers in generating values accurately.This decision support system was made using the MOORA method with ROC weighting where this method can be used or can be used as a reference in determining a problem because it aims to find out how many employees are Top Talent (Best Employee), after testing it is given a weight value on criteria and can be modified which aims to find out how many criteria will be added in each criterion which has its own weight value and after that a ranking is made in which the ranking can already determine the best BPN employee in the city of Medan, namely (T3) Anggi Alfarissi HSB with a score of 1,157. So because of this it was confirmed or very easy for the team to select in decision-making and were selected as the best BPN employees in the city of Medan.